Giant epidermal inclusion cyst masquerading as a soft tissue sarcoma - Hunter Phillips; Patrick Hogan; Devin Durica; Srikumar Pillai; Brett Mahon; David Lucero; James Cameron; Paul M. Kent (Elsevier, 2018)
Epidermal inclusion cysts (EIC) are common lesions formed by the invagination and cystic expansion of the epidermis or hair follicle. We present an unusual case of an epidermal inclusion cyst masquerading as a soft tissue sarcoma based on initial clinical presentation and radiographic findings. Mischaracterization of this type of lesion may lead to unnecessary diagnostic modalities or invasive, overly-aggressive surgery.